Unintentional endosulfan poisoning - (:unkn) unknown (COMENIUS UNIV, 2009)
Endosulfan is an organochloride insecticide, widely used in insect control, It is responsible for many severe intoxication and several deaths. We present a case series of endosulfan poisoning, admitted to our emergency department with different clinical courses. Two patients presented with status epilepticus and were successfully treated with thiopental sodium to control seizures. One patient required also hemodialysis. All patients were discharged following a complete recovery of their health. Endosulfan is a highly toxic insecticide that produces tonic-clonic convulsions, headache, dizziness and ataxia. It can cause also life threatening metabolic disturbances. Treatment is symptomatic and supportive (Tab. 2, Ref. 11). Full Text (Free, PDF) www.bmj.sk.
Keywords: emergency; endosulfan; hemodialysis; poisoning; status epilepticus; PESTICIDES